Hanging Ball and Handpad Drill Training: Which is better in improving the ability of the instep serve in Sepak Takraw? - Ummu Amalia Ulfa; Rohman Hidayat; Didik Rilastiyo Budi; Kusnandar Kusnandar; Panuwun Joko Nurcahyo (Sriwijaya Journal of Sport, 2024)
The Sepak Takraw game requires precise and programmed training to produce accurate serves. This research aims to determine the effect of hanging ball and hand pad drills (Target) on improving instep serviceability in Sepak Takraw. This research uses an experimental method with a two-group pretest-posttest design. Determination of the sample using the Total Sampling technique. The sample in this study consisted of 18 male athletes aged 16-20 years. The research instrument uses the sepak takraw instep service skill test. Testing in this research used SPSS version 26 with the classic assumption test using the normality test, homogeneity test, and hypothesis testing using the paired sample t-test and the independent sample t-test. The research results show that hanging ball drills and hand pad training significantly influence the ability of the Sepak Takraw instep serve with a Sig value. (2-tailed) of 0,000. A comparison of the results of hanging ball and handpad drills shows that hanging ball drills are more efficient in improving instep service than handpad drills as indicated by the Sig value. (2-tailed) 0,000. The research concludes that the hanging ball drill and handpad drill training methods can be used to improve the ability of instep serving techniques in sepak takraw athletes, through implementing an appropriate training program.